Disguised unemployment in an underdeveloped economy : its nature and measurement - Uppal, J. S. (New York : Asia Publishing House, 1973)
The study is divided into two parts: The first part is a comprehensive survey of the theory of disguised unemployment. The literature is organized into categories based on the main causes and forms of disguised unemployment. The material within each category is surveyed and the nature and logical foundations of the phenomenon are examined. The relevance of different categories of disguised unemployment is examined with reference to socioeconomic conditions in the rural sector of underdeveloped countries. The second part of the study is concerned with the measurement of disguised unemployment. Various techniques that have been applied to measure the phenomenon are described.
Bibliography: p. [127]-140.
rpm 17/04/2018
Loans
Keywords: Disguised unemployment; Agricultural laborers; Agricultural laborers